2022
DOI: 10.25301/jpda.313.114
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Calcium Hydroxide and Mineral Trioxide Aggregate in the Formation of Dentin Bridge – A Randomized Controlled Trial

Abstract: OBJECTIVE: This study is to compare the dentin bridge thickness achieved using calcium hydroxide and MTA using radiographs. METHODOLOGY: Single blinded randomized controlled trial conducted in the Operative Dentistry department at Fatima Jinnah Dental College and Hospital, Karachi. A total of 100 premolar and molar teeth with class I and II cavities were included in this study. The study participants were assigned into two groups, A and B of 50 participants each. Under local anesthesia, Group A was indirectly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…5 Formation of dentin bridge after DPC is an important factor in determining the outcomes of vital pulp therapy 24 as it protects the dental pulp from bacterial toxins and irritants, and helps in maintaining pulp vitality. 5,31 In our study, DPC of dogs' immature teeth showed formation of dentin bridge in 62.5 and 75% after the third and fourth months of capping with MTA, respectively. Parallel to our findings, Min et al 32 found that DPC of carries-free human third premolars with MTA caused formation of dentin bridge in all-capped teeth.…”
Section: Discussionsupporting
confidence: 53%
“…5 Formation of dentin bridge after DPC is an important factor in determining the outcomes of vital pulp therapy 24 as it protects the dental pulp from bacterial toxins and irritants, and helps in maintaining pulp vitality. 5,31 In our study, DPC of dogs' immature teeth showed formation of dentin bridge in 62.5 and 75% after the third and fourth months of capping with MTA, respectively. Parallel to our findings, Min et al 32 found that DPC of carries-free human third premolars with MTA caused formation of dentin bridge in all-capped teeth.…”
Section: Discussionsupporting
confidence: 53%